Nursing Students’ Cognitive Engagement in English Online Learning - Arfiani Indah Hayuningtias; Rihda Julian Ekaputra; Vebriyani Puji Lestari (Indonesian Educational Research Journal, 2025)
The transition to online learning in nursing education has presented considerable challenges in maintaining cognitive engagement, particularly in acquiring medical English, due to increased distractions and the lack of direct interpersonal interaction. This study aims to examine the factors that affect cognitive engagement in online English learning among nursing students. It identifies key challenges such as inadequate interaction with instructors, the difficulty of medical terminology, and the need for real-time feedback. The research was conducted through a survey of 101 nursing students across various study levels. Results indicate that while students appreciate the flexibility of online learning, maintaining cognitive engagement remains a challenge. Improvements in instructional design, particularly in enhancing interaction and feedback, are necessary to foster higher engagement and better learning outcomes.